How I became a qualitative researcher? - Scârneci, Florentina (Sociologija. Mintis ir veiksmas, 2012)
Abstract: The present article presents the personal experience of the author with research methodologies. Some limits of the social scientific research are being analyzed, regarding two of the stages of research: theoretical framework and operationalization; this is the way in which the validity of the criteria and the construct validity came into discussion. At the same time, the character of sociological theories and their utility in scientific research are under discussion. Reasons for which qualitative is chosen are listed despite the constant disapproval of this method in Romanian sociology (and it’s marginalization in Central – East Europe). The advantages of qualitative research in socio-human sciences are presented (what is being researched, through what methods, with what results). The special case of using the focus-group at a large scale is being analyzed (its use without following two of the major qualitative principals: theoretical sampling and theoretical saturation). The article advocates for the usage of qualitative and it is written in a personal and provocative style. Key words: sociological research methodology, qualitative research, quantitative research, validity. SANTRAUKA KODĖL AŠ PASIRINKAU KOKYBINIO TYRIMO BŪDĄ? Straipsnis parengtas remiantis asmenišku autorės, dirbančios tyrimo metodologijų srityje, patyrimu. Analizuojami sociologinio mokslinio tyrimo trūkumai, susiję su dviem tyrimo pakopomis: teorine struktūra ir operacionalizacija. Viena vertus, svarbu kriterijų ir konstrukcijų pagrįstumas, kita vertus, sociologinių teorijų taikymo moksliniams tyrimams patikimumas. Aptariamos kokybinio metodo pasirinkimo priežastys ir aplinkybės, rodančios, kad šis metodas Rumunijoje ir Centrinėje Rytų Europoje yra marginalizuojamas. Svarstomi įvairūs kokybinio metodo privalumai, įskaitant plačios apimties focus-grupių pavyzdžius. Straipsnio autorė nevengia kokybinio tyrimo būdo apologijos provokacinio stiliaus.